Effects of highest dose of sacubitril/valsartan association compared to lower doses on mortality and ventricular arrhythmias - Allain, Florent; Legallois, Damien; Blanchart, Katrien; Champ-Rigot, Laure; Pellissier, Arnaud; Ollitrault, Pierre; Chequel, Mathieu; Sabatier, Rémi; Lebon, Alain; Gomes, Sophie; Citerne, Olivier; Beygui, Farzin; et al. (Journal of Cardiology and Cardiovascular Medicine, 2020)
Background: Sudden cardiac death is a major healthcare issue in reduced ejection fraction heart failure (HFrEF) patients. Recently, the new association of sacubitril/valsartan showed a reduction of both ventricular arrhythmias (VA) and mortality even at low dose compared to enalapril in HF patients. The purpose of our study was to assess whether the highest dose of sacubitril/valsartan compared to lower doses may improve the rate of death and VA in a population of patients with HFrEF and with an implantable cardiac defibrillator (ICD). Methods: 104 HF patients with reduced EF under sacubitril/valsartan with an ICD were divided in 2 groups: the first one with the lower doses of sacubitril/valsartan (24/26 mg or 49 mg/51 mg twice daily) and the second with the maximal dose (97mg/103mg twice daily). The primary outcome was a composite of death or appropriate ICD therapy for VA. Results: After a median follow-up of 14 months, 39 patients were treated with lower doses and 65 patients with the highest dose. Patients from the lower doses group were older (70 [60-80] vs. 66 [60-70]; p = 0,03), more symptomatic at initiation (NYHA 3: 44% vs. 19%; p < 0,01) and more often in atrial fibrillation (31% vs. 12%; p = 0,04). The primary composite endpoint occurred in 14 patients (36%) in the low doses group versus 7 patients (11%) in high dose group (p < 0,01). This difference was particularly observed in the subgroup of patients with ischemic cardiomyopathy. In a multivariable analysis, the higher dose was independently associated with the primary outcome with an HR = 2,934 [IC 95% 1,147 – 7,504]; p = 0,03. Kaplan-Meier curve showed an early effect of the highest dose of sacubitril/valsartan association. Conclusion: Patients with HFrEF under the highest dose of sacubitril/valsartan showed better clinical outcomes with a decrease of both mortality or appropriated ICD therapies related to ventricular arrhythmias.